Sequence‐based typing identification of a novel allele HLA‐A*30:115. (13th June 2019) - Li, Xiaobo; Xu, Huifang; Mo, Xiaodong; Yang, Huanjie
Abstract : One nucleotide replacement at position 643 of HLA‐A*30:01:01 results in a novel allele, HLA‐A*30:115 .